The 39 clues. Unstoppable : Nowhere to run Vol.1 - Watson, Jude (New York Scholastic, 2013)
Thirteen-year-old Dan Cahill and his older sister, Amy, are the latest guardians of the Clues -- thirty-nine ingredients in a serum that transforms whomever takes it into the most powerful person on earth. They think they've done everything right, but a tiny mistake leads to catastrophe. The serum is missing and Dan and Amy have to get it back and stop who stole it ... before it's game over.
Keywords: Brothers and sisters -- Juvenile fiction; Secrecy -- Juvenile fiction; Secrets -- Fiction; Code and cipher stories; Adventure fiction